Reading Augustine's Confessiones in Fourteenth-Century England: John de Grandisson's Fashioning of Text and Self - Olson, Linda (Traditio, 1997)
We give to our church of Exeter [this book], which we labored much in correcting in Paris, in the hand of John of Exeter. And to this point I, John de Grandisson, have corrected, and not beyond, according to the book of Hugo of Saint Victor, as it was said to have been corrected by him, while I was studying in Paris, in the year of the Lord 1314, when the Templars were burned, in the next year after the Council of Vienne.